Expectation Gates Neural Facilitation of Emotional Words in Early Visual Areas - Trauer, Sophie M.; Müller, Matthias M.; Kotz, Sonja A. (Frontiers in Human Neuroscience, 2019)
The current study examined whether emotional expectations gate attention to emotional words in early visual cortex. Colour cues informed about word valence and onset latency. We observed a stimulus-preceding negativity (SPN) prior to the onset of cued words that was larger for negative than for neutral words. This indicates that emotional words are more anticipated than neutral words before target onset. During stimulus presentation the Steady-state visual evoked potential (SSVEP), elicited by flickering words, was attenuated for cued compared to uncued words, indicating sharpened sensory activity i.e. expectation suppression. Most importantly, the SSVEP was more enhanced for negative than neutral words when these were cued. Uncued conditions did not differ in SSVEP amplitudes, paralleling previous studies reporting lexico-semantic but not early visual effects of emotional words. We suggest that cueing mediates the capture of visual resources by providing an early ‘emotional gist’ of an upcoming word. Consequently, visual single-word studies may have underestimated attentional effects of emotional words and their anticipation during reading.